Measuring the adoption of ICT levels and the perceived impact on performance within the SME manufacturing sector in South Africa - Motsoeneng, Lerato (My University, 2014)
The establishment and growth of Small Medium Enterprises (SMEs) in most economies have been attributed with a corresponding need and desire for these SMEs as catalysts for economic growth, unemployment reduction, etc. Various factors are also impacting on how SMEs can become competitive and one of these enablers is the adoption of ICT by SMEs to improve performance. The purpose of this research was to establish the perceived relationship between the adoption by SMEs of Information Communication Technology (ICT) usage in the manufacturing sector in South Africa and its perceived impact on firm performance. The intended objective was to assess whether the perception of ICT adoption usage within SME’s operating within a manufacturing sector will either have a positive or negative performance outcome. The research methodology adopted was a quantitative approach which was guided by a positivist paradigm. The population targeted were SMEs in the manufacturing sector in South Africa but deliberately excluded SME manufacturers involved in the production of computers, electronics, etc. A combination of an online survey and paper questionnaire was utilised to gather data. The adoption of ICT and the perceived impact on performance within SMEs in manufacturing in South Africa revealed some findings consistent with existing literature in terms of the overall accepted perception that ICT adoption has a perceived positive impact on firm performance, including but also not limited to market share, products and service innovation, etc. as measured in the research. A deeper analysis is required to understand why the respondents in the research did not overwhelmingly state that ICT adoption has a perceived positive impact on performance, market share, product and service innovation etc.
Thesis (M.M. (Entrepreneurship and New Venture Creation))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2014.
Keywords: Small business; Information communication technology; Performance; Manufacturing sector